World's First Thermoelectric Generator Made of Tailored Carbon Allotropes. Issue 9 (5th May 2020) - Borchardt, Rudolf; Fromm, Timo; Haase, Armin; Fecher, Jonas; Rosiwal, Stefan M.
Abstract : Carbon and carbon‐based compounds are today's mostly used sources of energy. By burning them, their chemically stored energy can be transformed to mechanical energy and further on to electrical energy. These transformation steps entail huge thermal losses. Thermoelectric generators (TEGs) are devices that allow the direct conversion of thermal gradients into electrical energy through a smart combination of n‐ and p‐conducting materials and are therefore an appealing approach to tackle thermal losses. However, the materials in today's TEGs, e.g., Bi2 Te3, show limited thermal stability and often are toxic or not abundantly available which only allow for niche applications like military and aerospace equipment. Herein, the fabrication of the first, fully functional all‐carbon TEG is shown. The used carbon materials, made by chemical vapor deposition (CVD) processes, are both, nontoxic and abundant, and potentially paves the way for the large‐scale use of TEGs. Not only the thermal losses of conventional combustion processes but also thermal gradients established by solar thermal systems are potential fields of application. The assay is anticipated to spark further interest in carbon‐based thermoelectric materials. Such materials can be produced on a large scale and combined to a fully functional thermoelectric device. Abstract : Thermoelectric generators (TEGs) are appealing approaches to tackle thermal losses by direct conversion of thermal gradients into electrical energy. Today's TEGs are mainly made of materials that are rare, partially toxic, and have an insufficient long‐term temperature stability. Therefore, there is a need for novel and improved thermoelectric materials. Herein, insights into recent developments of carbon‐based thermoelectric materials are shown.